Influencia del Burnout, la calidad de vida y los factores socioeconómicos en las estrategias de afrontamiento utilizadas por los profesionales y auxiliares de enfermería - Contreras , Francoise (2022)
The aim of this study was to evaluate the influence of the Burnout syndrome and quality of life, as well as the socioeconomic variables in the coping styles used by 71 health workers (52.1 % nurses and 47.9 % nursing aids). The health questionnaire (SF36), the stress coping questionnaire (CAE) and the Maslach Burnout Inventory (MBI) were applied. According to the results, the presence of Burnout was low (77.5 % without Burnout), the quality of life was reduced in the areas of vitality, corporal pain and general health, and the most used strategies were those of focusing on the solution of problems and positive reappraisal. The increase in the quality of life, the reduction in the severity of Burnout symptoms, being female, young and working as a nurse, are all significant predictors (cubic regression) of the increase in the use of all the coping strategies, especially those focusing on the solution of problems and positive reappraisal.